Africa's Pulse, October 2015 - Chuhan-Pole, Punam (World Bank, Washington, DC, 2015)
External headwinds and domestic difficulties are impacting economic activity in Sub-Saharan Africa. Sub-Saharan Africa’s growth will decelerate in 2015 amid weak global economic conditions. Some countries, however, will continue posting solid growth. Sub-Saharan Africa is entering a period of tightening borrowing conditions amid growing domestic and external vulnerabilities. Reflecting the widening fiscal deficits, government debt has continued to rise in many countries. Weak fundamentals, combined with the strong appreciation of the U.S. dollar, have kept currencies across the region under pressure throughout the year. Policy buffers are low in several countries, constraining the response to the current environment and underscoring the need for African countries to improve domestic resource mobilization and enhance public expenditure efficiency. Progress in reducing income poverty in Sub-Saharan Africa may have been faster than the authors thought, but poverty remains high. The region’s growth deceleration challenges efforts to reduce poverty.